Effect of free-weight vs. machine-based strength training on maximal strength, hypertrophy and jump performance - a systematic review and meta-analysis - Haugen, M. E.; Vårvik, F. T.; Larsen, S.; Haugen, A. S.; van den Tillaar, R.; Bjørnsen, T. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background The effectiveness of strength training with free-weight vs. machine equipment is heavily debated. Thus, the purpose of this meta-analysis was to summarize the data on the effect of free-weight versus machine-based strength training on maximal strength, jump height and hypertrophy.